Władze Uniwersytetu Papieskiego Jana Pawła II w Krakowie - Dyduch, Jan (Analecta Cracoviensia, 2013)
The Pontifical University of John Paul II in Cracow is an ecclesiastical university. The Apostolic Constitution Sapientia christiana and the statute of the university regulate its governance. The collegial bodies and the natural persons exercise the authority in question. Among the first group one can count: the Congregation for Catholic Education, the Polish Episcopal Conference, the University Senate; while the second category consists of: the Great Chancellor, the vice Great Chancellor, Rector, and deans of faculties.